2016
DOI: 10.3390/molecules21060683
|View full text |Cite
|
Sign up to set email alerts
|

Clematichinenoside (AR) Attenuates Hypoxia/Reoxygenation-Induced H9c2 Cardiomyocyte Apoptosis via a Mitochondria-Mediated Signaling Pathway

Abstract: Abstract:Mitochondria-mediated cardiomyocyte apoptosis is involved in myocardial ischemia/reperfusion (MI/R) injury. Clematichinenoside (AR) is a triterpenoid saponin isolated from the roots of Clematis chinensis with antioxidant and anti-inflammatory cardioprotection effects against MI/R injury, yet the anti-apoptotic effect and underlying mechanisms of AR in MI/R injury remain unclear. We hypothesize that AR may improve mitochondrial function to inhibit MI/R-induced cardiomyocyte apoptosis. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
8
1
Order By: Relevance
“…Bcl-2 and Bax are the major members of the Bcl-2 protein family, which are involved in mitochondrion-mediated apoptosis. The former demonstrates an anti-apoptotic effect, whereas the latter exhibits a pro-apoptotic effect (29). In the present study, the expression of Bcl-2 was downregulated by hypoxia/reoxygenation in contrast to that in the control group.…”
Section: Effect Of Eriodictyol On Caspase-3 Activity and Expression Lcontrasting
confidence: 54%
“…Bcl-2 and Bax are the major members of the Bcl-2 protein family, which are involved in mitochondrion-mediated apoptosis. The former demonstrates an anti-apoptotic effect, whereas the latter exhibits a pro-apoptotic effect (29). In the present study, the expression of Bcl-2 was downregulated by hypoxia/reoxygenation in contrast to that in the control group.…”
Section: Effect Of Eriodictyol On Caspase-3 Activity and Expression Lcontrasting
confidence: 54%
“…Previous findings have suggested that gypenoside protects the cardiomyocytes against the injury via the mitogen-activated protein kinase-mediated nuclear factor-κB pathway (26). In addition, as the convergent pathway of final ischemia and reperfusion injury, mitochondria-mediated apoptosis has been demonstrated to be involved in protective effects of most phytochemicals, including clematichinenoside (27) and ilexsaponin A (28).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AR has been demonstrated to attenuate I/R injury. Ding et al reported that AR ameliorates myocardial I/R injury in H9c2 cardiomyocytes through the mitochondrial‐mediated apoptotic signalling pathway. However, the effect of AR on renal I/R injury remains unclear.…”
Section: Introductionmentioning
confidence: 99%